The association between flagellin producers in the gut microbiota and HDL-C level in humans - Yiu, Jensen H. C.; Cai, Jieling; Cheung, Samson W. M.; Chin, Karie Tsz-Ching; Chan, Chi Fai; Ma, Edward S.C.; Sharma, Rakesh; Dorweiler, Bernhard; Woo, Connie W. (Frontiers in Microbiomes, 2023)
The gut microbiota can be beneficial and harmful to cardiovascular health depending on the mechanisms. The interaction between gut microbiota-derived flagellin and toll-like receptor 5 in hepatocytes, resulting in apolipoprotein A1 (ApoA1) production, brings forth a cardiovascular benefit to the host. Here, the association between flagellated microbiota and high-density lipoprotein-cholesterol (HDL-C) in humans was explored. Through sex-based gut microbiota analysis of two population-based cohorts, the 500 Functional Genomics Project (500FG) and Chinese cohorts, we found positive correlations between the capacity to produce flagellins in the gut microbiota and HDL-C in females of the 500FG and males of Chinese cohorts. Eubacterium rectale, Lachnospira pectinoschiza, Roseburia intestinalis and Roseburia inulinivorans were crucial species for such correlations. Diverse types of flagellins and TLR5, but not NAIP/NLRC4, flagellin-engaging receptors, were detectable by proteomic analysis of the human liver. However, not all flagellated bacteria yield the same degree of such benefit because of differences in the penetration of flagellins where other factors such as geographics and diets may play important roles.